Cultural Adaptation and Environmental Challenges: A Case Study of Nubian Communities in Egypt through the Lens of Cultural Ecology Theory - Wicaksono, Imam; alGayyar, Sherif Sa’ad; Hassan, Ahmed Hassan Mohammad (Journal Of Middle East and Islamic Studies, 2024)
The purpose of this study is to investigate how the ecological changes brought about by the building of the Aswan Dam have affected the Nubian community's social structure, cultural identity, and coping mechanisms. The study emphasizes how important it is to comprehend how people interact with their surroundings considering modernization, which frequently jeopardizes the viability of regional customs. In addition to a literature review approach, a thematic analysis grounded in Julian Steward's cultural ecology theory—which highlights how societies adjust to changes in their physical surroundings—was used. The results show that ecological changes have profoundly impacted the Nubian people's cultural rites, cooperative social structures, and traditional farming methods. In response to these constraints, the Nubian community has adopted adaptive tactics to sustain its livelihoods, such as diversifying its economy, preserving its indigenous customs and the arts, and incorporating contemporary technologies. This work makes a theoretical contribution by extending the application of cultural ecology theory to the setting of modernization that upends regional customs and cultures. It also offers useful ramifications for formulating policies that combine sustainable and interconnected natural resource management with the preservation of regional culture.